Molecular Detection of Virulence Genes Fimh and Csga in Salmonella Typhi Isolated From Stool Samples - Hassan, Riyam Wissam (American Journal of Biology and Natural Sciences, 2026)
Background: Gram-negative Salmonella typhi, a bacterium that causes intestinal diseases, including typhoid fever, as a consequence of ingesting foods and drinks contaminated by this bacterium. Salmonella typhi uses various virulence factors like, cilia and filaments and fibers that are used in the adhesion and invasion of its host cells. Objective: This study aimed to isolate, diagnose and investigate the extent of Salmonella typhi in stool samples of patients suffering from typhoid fever. In addition, to the identification of virulence genes fimH and csgA, which provide the ability for Salmonella typhi to adhere and help in the formation of biofilms. Methodology: 250 stool samples were collected in plastic containers from patients visiting hospitals in Al- Diwaniyah city who were suffering from typhoid fever. The samples were then transferred to the laboratory and cultured in a mediums supported the growth of Salmonella. The diagnosis was made using a range of diagnostic and biochemical tests, in addition to Vitek system and serological tests. After the extraction of DNA, the virulence genes fimH and csgA of Salmonella typhi isolates were studies using PCR techniques. Results: According to the results showed that 176 (69.6%) stool samples showed a positive result for growth on culture media used in the study, while 76 (30.4%) showed a negative result for culture. and out of 174 positive stool samples of typhoid patients, 20 (11.4%) stool samples contained Salmonella typhi. Analysis the results of the PCR method to detect the genes showed that 100% of the isolates contained the fimH gene, and 35% of Salmonella typhi isolates contained the csgA gene. Conclusions: Salmonella typhi was found to be a pathogen because it resulted in infection, it was isolated from 11.4% of typhoid fever patients, fimH is the most dominant gene with a 100% rate, and the gene csgA has a rate of 35%.